Functional characterization of Caenorhabditis elegans cbs-2 gene during meiosis - Santonicola, Pamela (Sci Rep, 2020)
Cystathionine β-synthase (CBS) is a eukaryotic enzyme that maintains the cellular homocysteine homeostasis and catalyzes the conversion of homocysteine to L-cystathionine and Hydrogen sulfide, via the trans-sulfuration pathway. In Caenorhabditis elegans, two cbs genes are present: cbs-1 functions similarly as to human CBS, and cbs-2, whose roles are instead unknown. In the present study we performed a phenotypic characterization of the cbs-2 mutant. The null cbs-2 mutant is viable, fertile and shows the wild-type complement of six bivalents in most oocyte nuclei, which is indicative of a correct formation of crossover recombination. In absence of synaptonemal complex formation (syp-2 mutant), loss of cbs-2 leads to chromosome fragmentation, suggesting that cbs-2 is essential during inter-sister repair. Interestingly, although proficient in the activation of the DNA damage checkpoint after exposure to genotoxic stress, the cbs-2 mutant is defective in DNA damage-induced apoptosis in meiotic germ cells. These results suggest possible functions for CBS-2 in meiosis, distinct from a role in the trans-sulfuration pathway. We propose that the C. elegans CBS-2 protein is required for both inter-sister repair and execution of DNA damage-induced apoptosis.